Early prostaglandin E1 treatment improves visual outcomes in central retinal artery occlusion: a retrospective study - Sano, Hiroki; Yanai, Ryoji; Kondo, Hirotaka; Mitamura, Yoshinori (Frontiers in Ophthalmology, 2025)
BackgroundCentral retinal artery occlusion (CRAO) is a vision-threatening emergency with no established effective treatment. Prostaglandin E1 (PGE1), known for its vasodilatory and cytoprotective properties, may offer therapeutic benefits for retinal ischemia.MethodsIn this retrospective study, we compared visual outcomes between CRAO patients who received intravenous PGE1 within 24 hours of symptom onset (followed by oral administration) and those who received conventional therapy. PGE1 was administered intravenously for 5 days.ResultsAt one month, the PGE1 group showed significantly better best-corrected visual acuity compared to the control group. Baseline structural retinal parameters, including maximal retinal thickness (MRT) and central retinal thickness (CRT), did not differ significantly between groups. In the PGE1 group, baseline MRT was negatively correlated with visual acuity at one month. Retinal arteriovenous diameters showed no significant change post-treatment. No adverse events were observed in either group.ConclusionEarly administration of PGE1 may improve visual outcomes in CRAO. These findings support further investigation into PGE1 as a potential treatment for acute retinal ischemia.